Utilization of household waste to support the integrated sustainable food house area in Kalirejo Village - Sulis Dyah Candra; Judi Suharsono; Meliana Putri; Ahmad Rizal Sultoni (Universitas Muhammadiyah Magelang, 2023)
The community in Kalirejo Village is still not fully optimizing the utilization of household waste, both inorganic and organic waste, which can support the success of the Sustainable Food Home Area (KRPL) program. This program aims to enhance understanding, abilities, and good practices in waste utilization within households. The program is implemented through several stages, including training, mentoring, socialization, and monitoring. The results show that people have gained an understanding of basic techniques for simple hydroponic cultivation using a wick system. Furthermore, individuals are capable of producing Bokashi fertilizer from organic waste and are knowledgeable about the methods for creating pokak drinks using onion skin waste, along with understanding the associated health benefits.